Constitutive Relations for Ti-6Al-4V Hot Working. (2017) - Jha, Jyoti S.; Tewari, Asim; Mishra, Sushil; Toppo, Suraj
Abstract: The alpha-beta Titanium alloy (Ti-6Al-4V) is the most common alloy in the aerospace industry. The hot workability of Ti–6Al–4V with lamellar microstructure has been investigated by means of compression tests carried out in the 750–950 0 C temperature range and 0.001–10s -1 strain rate range in the Gleeble 3800. The stress-strain data obtained from the compression test results have been processed to develop the Arrhenius and Norton-Hoff constitutive models. The Arrhenius model is strain independent; however, Norton-Hoff constitutive model better predict the flow stress, which decreases with the increase in strain. The decrease in the flow stress is attributed to the kinking and globularization of initial lamellar microstructure; however, the breakdown of microstructuredepends on the processing strain, strain rates and temperature. Microstructure analyses have been done to correlate the strain, strain rate, temperature with the change in the microstructure.